Terrorism in Indonesian literature and film: A psychological perspective through readers' responses - Ahmadi, Anas; Yani, Muhammad Turhan; Savira, Siti Ina; Suhartono, Suhartono (Edelweiss Applied Science and Technology, 2025)
Terrorism is currently being discussed and researched on a global scale because it is controversial in various countries. On the one hand, terrorism is considered a trigger for war. On the other hand, it is viewed as an impact of the global world. In this regard, this research aims to explore terrorism in Indonesian literature and film from the perspective of reader responses. The theory used in this research is a psychological study of reader response, which adapts Iser's thinking. The method employed is qualitative. The respondents are 200 teenagers (ages 18-20 years). The data collection techniques used were questionnaires and interviews. The research results show that, first, in relation to readability, more than 50 percent of respondents have read and watched Indonesian films related to terrorism. Second, Indonesian literature and films related to terrorism are closely connected to psychology. Third, these works have a psychological influence on their readers. For this reason, Indonesian literature and films related to terrorism actually have more positive aspects than negative ones. Fourth, from the aspect of reader responses related to criticism of Indonesian literature and films, the theme of terrorism serves to eliminate stereotypes in film representation.